PRAKTIK BARTER PADI DENGAN BERAS DI KELURAHAN PEJERUK KECAMATAN AMPENAN PERSPEKTIF HUKUM ISLAM - Fitriyani; Muhammad Nor (Universitas Islam Negeri Mataram, 2021)
Bartering paddy for rice is an exchange that often occurs among people, for example they exchange paddy for rice and vice versa. Meanwhile, paddy and rice are the same basic food ingredients. The only thing that differentiates paddy from rice is the processing process. Problems like this are still often experienced by people in the subdistrict where researchers carry out research because the community has its own considerations so they exchange similar food ingredients.